Increased fungal burden in the gastrointestinal tract of brain-dead organ donors - Erika J. Nachman; Colleen K. Ardis; A. Kyle B. Ardis; Javier Nieto; Madeline M. Bresson; Clare M. Robertson; Maggie N. Seale; Nora M. Villafuerte; Zhe Lyu; Eva C. Preisner; Heather A. Danhof; Sara C. Di Rienzi; et al. (Microbiology Spectrum)
ABSTRACT Approximately 3% of organ transplant recipients will be diagnosed with an invasive fungal infection (IFI), with 10%–47% being fatal. The source of IFI is typically not known, but Candida spp. cause the majority of IFI cases. We obtained intestines from two types of organ donors, brain-dead (BD) (n = 7) and donation after circulatory death (DCD) (n = 5), to sample microbes from the mucosal surface and the lumen. BD donors were parenterally fed and treated with corticosteroids in the days before procurement, whereas DCD donors were enterally fed and not given corticosteroids. We found fungi present in 81% of BD donor samples compared to 31% of DCD donor samples. The fungal load was significantly increased in most of the intestinal sites in BD donor samples over DCD donor samples. We recovered 12 isolates of Candida albicans, 10 isolates of Nakaseomyces glabratus, and one isolate of Candida tropicalis from the human intestine of nine organ donors. Sequence analysis revealed a high prevalence of gene families associated with virulence and drug resistance, the latter of which was corroborated by antifungal resistance testing. Overall, this study provides evidence of increased fungal presence in BD donors compared to DCD donors, which suggests that corticosteroid administration and parenteral feeding strategies of BD donors may impact the burden of IFI in transplant recipients.IMPORTANCEInvasive fungal infections pose a significant risk to organ donor recipients, and the sources of these fungal infections are mostly unknown. Our study investigated fungal differences in the gastrointestinal tract between two types of organ donors: brain-dead and donation by circulatory death, for the first time. We found that brain-dead donors had a significant increase in the frequency and abundance of fungi throughout the gastrointestinal tract. We speculate that differences in care, such as corticosteroid administration and feeding methods before organ procurement, may begin to explain the difference in fungal presence between the donors. We propose further studies into the administration of steroids and delivery of nutrients to organ donors before procurement to impact fungal load and reduce life-threatening invasive fungal infections in the recipients.